USE OF ULTRASOUND EXAMINATION AS A METHOD OF DIAGNOSING URINARY BLADDER PATHOLOGIES OF SMALL ANIMALS - Kulynych, S. M.; Dehnych, I. S.; Zvenihorodska, T. V. (Scientific Progress & Innovations, 2021)
Ultrasound diagnostics in veterinary medicine has become widespread in Ukraine in the recent decade. More and more often the owners of veterinary clinics for small animals install ultrasound equipment, not always realizing the possibilities of ultrasonography in diagnosing and the necessity to possess certain skills and abilities of the staff to operate it. That is why the purpose of our study was to find out which of the uri-nary bladder pathologies are most often detected by ultrasound examination and what place they occupy among the pathologies of the urinary system, as well as to determine how ultrasonographic changes in the urinary bladder correspond to physical and chemical examination of urine at diagnostics. The tests were conducted on 30 dogs and 62 cats aged from 1 to 15 years old, having the following clinical features: pain at palpation in the urinary bladder area, hematuria, and dysuria. We used ultrasound equipment: Aloka 31 F (Japan) and Esaote mylab one (Italy), Micro-convex SC3123 and linear UST-5512U transducers with 5-7.5 MHz frequency. Cystitis and urolithiasis were revealed as the most common pathologies during ultraso-nographic examination of the urinary bladder in dogs and cats. Cystitis in most cases was manifested by hy-per-echogenicity of the urinary bladder walls and their thickening. In 60 % of cats having the urinary blad-der wall thickening, a slight thickening was observed, while in 40 % of cats the thickening was significant (up to 3.7 mm at a rate of up to 1.7 mm). In all dogs with the urinary bladder wall thickening, the thickening was significant (3.4±0.4 mm). Urolithiasis manifested itself in the form of hyper-echogenic opalescent sus-pension in the lumen of the urinary bladder or hyper-echogenic calculi that made a clear echo-acoustic shadow. Ultrasonographic changes were confirmed by laboratory testing. At animal cystitis, changes of col-or, smell, pH of urine, proteinuria, leukocyturia, hematuria, bilirubinuria were registered. Urine sediment study showed that urates were detected in 54.4 % of cats with ultrasonographic signs of urolithiasis and struvites were detected in 63.6 % of dogs.